Sodium and water handling during hemodialysis: new pathophysiologic insights and management approaches for improving outcomes in end-stage kidney disease - Canaud, Bernard; Kooman, Jeroen; Selby, Nicholas M.; Taal, Maarten; Francis, Susan; Kopperschmidt, Pascal; Maierhofer, Andreas; Kotanko, Peter; Titze, Jens (Kidney International, 2019)
Space medicine and new technology such as magnetic resonance imaging of tissue sodium stores ((NaMRI)-Na-23) have changed our understanding of human sodium homeostasis and pathophysiology. It has become evident that body sodium comprises 3 main components. Two compartments have been traditionally recognized, namely one that is circulating and systemically active via its osmotic action, and one slowly exchangeable pool located in the bones. The third, recently described pool represents sodium stored in skin and muscle interstitium, and it is implicated in cell and biologic activities via local hypertonicity and sodium clearance mechanisms. This in-depth review provides a comprehensive view on the pathophysiology and existing knowledge gaps of systemic hemodynamic and tissue sodium accumulation in dialysis patients. Furthermore, we discuss how the combination of novel technologies to quantitate tissue salt accumulation (e.g., (NaMRI)-Na-23) with devices to facilitate the precise attainment of a prescribed hemodialytic sodium mass balance (e.g., sodium and water balancing modules) will improve our therapeutic approach to sodium management in dialysis patients. While prospective studies are required, we think that these new diagnostic and sodium balancing tools will enhance our ability to pursue more personalized therapeutic interventions on sodium and water management, with the eventual goal of improving dialysis patient outcomes.
CRIS-Team WoS Importer:2020-02-21